The Phenotype Variability, of the Racka Sheep in the Republic of Serbia - PIHLER, I.; ĆIRIĆ, J.; KUČEVIĆ, D.; DRAGIN, S.; AL-HASANT, M.; ŠARAN, M.; ZARUBICA, B.; TSAKMAKIDIS, I.A. (Journal of the Hellenic Veterinary Medical Society, 2020)
The intensification of sheep production, by permanent genetic selection and the development of breeding technology, has led to the creation of highly productive sheep breeds. In this way, many highly productive breeds were created which could demonstrate their high production potentials only under perfect conditions of nutrition, accommodation and care. Preservation of indigenous breeds is of great importance in order to protect and safeguard those breeds and, in this way, it is possible to restore some of the characteristics that are lost during intensive selection, which are mostly related to resistance. The Racka sheep (Serbian: Vitoroga žuja) is considered to be an autochthonous breed and a genetic resource in the Republic of Serbia. As a primitive breed with low productivity, it offers no economic profitability and, thus, there is no great interest in its breeding. According to the FAO data from 2008-2014, the number of these sheep ranges from 500 to 1000. The objective of this study was to determine the phenotypic variability and to assess the external measurements of the Racka sheep. One-hundred fifty Racka breed ewes were included in this study. The effects of three farms on the phenotypic characteristics and their body indexes were calculated. The significance of the research is reflected in the advancement of this breed and in the assessment of the possibilities of selection work in these herds.